Konsentrasi Asam Lemak Terbang dan Glukosa Darah Domba Ekor Tipis yang Diberi Bungkil Kedelai Terproteksi Tanin (VOLATILE FATTY ACID CONCENTRATION AND BLOOD GLUCOSE ON THIN-TAILED SHEEP GIVEN WITH TANINE-PROTECTED SOYBEAN MEAL) - Nuraliah, Siti; Purnomoadi, Agung; Nuswantara, Limbang Kustiawan (Jurnal Veteriner; Vol 16 No 3 (2015), 2015)
This study aims to analyze the influence of tannin-protected protein source feed to livestock productivitybased on its influence on methane production, Volatile fatty acids (VFA) production, and blood glucose inthe use of tannin-protected protein on complete feed in thin-tailed ram. The study uses thin-tailed ramaged about 8 months, as many as 16 rams with body weight of 11.81±1.65 kg. The researchusesa completerandomized design(CRD) withfour treatmentsandfourreplications. The treatments areP0:15% soybeanmeals without tannin protection in complete feed, P1:15% soybean meals with 0.5% tannin protection incomplete feed, P2:15% soybean meals with 1% tannin protection in complete feed and P3:15% soybeanmeals with 1.5% tannin protection in complete feed. The results indicates that administration of tanninsin soybean meal in complete feed showed significant effect (P <0.05) on blood glucose, the production ofpropionic acid in the 3rd hour, but the VFA production at hour 0, hour 6, as well as methane productionshowed no significant effect (P> 0.05). The conclusion is that 15% protected soybean meal with 1% oftannin in the complete feed is able to contribute to the proportion of propionate and contribute to increasedblood glucose on a thin-tailed ram but can not to reduce methane production.
Keywords: soybean meal, tannin, volatile fatty acid (VFA), blood glucose, methane